Juridical Analysis of the Difference in Judges' Considerations in First-Instance Decisions and Cassation Against Persecution Resulting in Death Based on the Principle of Justice: (Study of Decision Number 1466 K/Pid/2024 jo. Decision Number 454/Pid.B/2024/PN. Sby) - Lesmana, Sri Jaya; Hendriansyah, Gilang; Indayatun, Ratna (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
The significant differences in judges' decisions reflect a serious challenge to the principle of equality before the law and public trust in the justice system. In general, this difference occurs due to a variety of factors. This study examines the difference in judges' considerations in “Decision Number 454/Pid.B/2024/PN Surabaya” (first level) and “Cassation Decision Number 1466/K/Pid/2024 Supreme Court” in cases of persecution resulting in death. The focus of the research is the trajectory of the shift from a free verdict to a guilty verdict, by assessing the application of the principles of justice and legal certainty (Radbruch theory). The research method is normative juridical, based on document studies. The results of the study showed that at the first level, the panel of judges focused on CCTV footage and traffic expert testimony, using the principle of in dubio pro reo, but ignoring key evidence such as visum and vehicle tracks. As a result, the verdict tends to only meet procedural certainty without substantive justice. On the other hand, the Supreme Court in cassation developed a comprehensive analysis of the assessment of evidence which included medical, visual, forensic, and chronological evidence, so that the element of conditional intentionality and a complete causal relationship were found. Thus, cassation decisions display a harmonized approach between legal certainty, utility, and substantive justice, in accordance with the Radbruch principle that prioritizes justice when formal law causes injustice. The researcher suggests that judicial guidelines be made in the assessment of evidence and intensive training in criminal law theory, so that judges' considerations at the initial level are more consistent, transparent, and able to reach the dimension of substantive justice, while increasing the legitimacy of criminal justice in Indonesia.